2009
DOI: 10.1021/ic9014916
|View full text |Cite
|
Sign up to set email alerts
|

Discovering the Complex Chemistry of a Simple NiII/H3L System: Magnetostructural Characterization and DFT Calculations of Di- and Polynuclear Nickel(II) Compounds

Abstract: The simple nickel(II) acetate/H(3)L system (H(3)L = 2-(2-hydroxyphenyl)-1,3-bis[4-(2-hydroxyphenyl)-3-azabut-3-enyl]-1,3-imidazolidine) presents an unusually complicated reactivity scheme, which strongly depends on the Ni(OAc)(2)/H(3)L molar ratio and on the pH of the medium. Thus, in addition to the formerly reported compounds [Ni(2)L(OAc)(H(2)O)(2)][Ni(2)L(OAc)(H(2)O)(HOAc)].3.25H(2)O, 1.3.25H(2)O; [{Ni(3)L(OAc)(OH)(H(2)O)(MeOH)(2)}(CO(3)){Ni(2)L(OAc)(MeOH)(2)}].2.7H(2)O.1.5MeOH, 2.2.7H(2)O.1.5MeOH; and [Ni(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 63 publications
0
21
1
Order By: Relevance
“…Despite the high stability shown by this type of three-armed ligands when we had worked with them ( [11,12] and own references therein), the reason for these fruitless results could be related to reaction and/or crystallisation periods longer than usual, with a partial decomposition of H3L. This fact had been previously detected for another related ligand [18]. Unfortunately, the lack of a sufficient amount of sample, with a guaranteed purity, prevented us from performing further studies of this complex.…”
Section: Synthetic Methodsmentioning
confidence: 88%
“…Despite the high stability shown by this type of three-armed ligands when we had worked with them ( [11,12] and own references therein), the reason for these fruitless results could be related to reaction and/or crystallisation periods longer than usual, with a partial decomposition of H3L. This fact had been previously detected for another related ligand [18]. Unfortunately, the lack of a sufficient amount of sample, with a guaranteed purity, prevented us from performing further studies of this complex.…”
Section: Synthetic Methodsmentioning
confidence: 88%
“…For dinuclear nickel compounds containing ligands with a predefined ground state, see: Fondo et al (2005Fondo et al ( , 2007Fondo et al ( , 2009 ; ;; Lu et al (2007); Paital et al (2007Paital et al ( , 2009. For density functional theory (DFT) calculations, see: Fondo et al (2005).…”
Section: Related Literaturementioning
confidence: 99%
“…Nickel complexes of the compartmental triprotic heptadentate ligand, 2-hydroxyphenyl)-1,3-bis[4-(2-hydroxyphenyl)-3-azabut-3-enyl]-1,3-imidazolidine and its derivatives have been of interest for their ability to give rise to dinuclear compounds with a predefined ground state (Fondo et al, 2005(Fondo et al, , 2007(Fondo et al, , 2009Lu et al, 2007;Paital, et al, 2007Paital, et al, , 2009. Density functional theory (DFT) calculations demonstrated that the Schiff base provides an NCN bridge between the metal ions that helps to mediate the ferromagnetic exchange (Fondo, et al, 2005).…”
Section: Commentmentioning
confidence: 99%
“…For nickel complexes of similar ligands, see: Fondo et al (2005Fondo et al ( , 2006aFondo et al ( ,b, 2007Fondo et al ( , 2009 ;Khan et al (2011); Lu et al (2007); Paital et al (2007Paital et al ( , 2009).…”
Section: Related Literaturementioning
confidence: 99%
“…Data collection: SMART (Bruker, 2000); cell refinement: SAINT-Plus (Bruker, 2000); data reduction: SAINT-Plus; program(s) used to solve structure: SHELXS97 (Sheldrick, 2008); program(s) used to refine structure: SHELXL97 (Sheldrick, 2008); molecular graphics: SHELXTL (Sheldrick, 2008); software used to prepare material for publication: SHELXTL. compounds with a predefined ground state (Fondo et al, 2005(Fondo et al, , 2006a(Fondo et al, ,b, 2007(Fondo et al, , 2009Lu et al, 2007;Paital, et al, 2007Paital, et al, , 2009). Density functional theory (DFT) calculations demonstrated that the Schiff base provides an NCN bridge between the metal ions that helps to mediate the ferromagnetic exchange (Fondo, et al, 2005).…”
Section: Data Collectionmentioning
confidence: 99%